Nutraceutic Potential of Bioactive Compounds of Eugenia dysenterica DC in Metabolic Alterations - Santana, Lidiani Figueiredo; Sasso, Sandramara; Aquino, Diana Figueiredo Santana; de Cássia Freitas, Karine; de Cássia Avellaneda Guimarães, Rita; Pott, Arnildo; do Nascimento, Valter Aragão; Bogo, Danielle; de Oliveira Figueiredo, Patrícia; Hiane, Priscila Aiko (Molecules (Basel, Switzerland), 2022)
The fruit and leaves of Eugenia dysenterica DC., locally known as cagaita, are rich in antioxidant glycosylated quercetin derivatives and phenolic compounds that have beneficial effects on diabetes mellitus, hypertension and general inflammation. We conducted a literature search to investigate the nutraceutical potentials of these phenolic compounds for treating obesity, diabetes mellitus and intestinal inflammatory disease. The phenolic compounds in E. dysenterica have demonstrated effects on carbohydrate metabolism, which can prevent the development of these chronic diseases and reduce LDL (low-density lipoprotein) cholesterol and hypertension. E. dysenterica also improves intestinal motility and microbiota and protects gastric mucosa, thereby preventing inflammation. However, studies are necessary to identify the mechanism by which E. dysenterica nutraceutical compounds act on such pathological processes to support future research.